Preliminary Proof-of-Concept Testing of Novel Antimicrobial Heat-Conducting “Metallic” Coatings Against Biofouling and Biocorrosion - Wang, Di; Hall, Timothy D.; Gu, Tingyue (Frontiers in Microbiology, 2022)
NiMo (nickel-molybdenum) and NiMo with embedded CeO2 nanoparticles (NPs) (100 nm) were tested as antimicrobial coatings (~15 µm thickness) on titanium (Ti) surfaces using an electrochemical process for heat exchanger applications onboard marine vessels. Preliminary static biofouling and biocorrosion (also known as microbiologically influenced corrosion) assessments were carried out in glass bottles using pure-culture Desulfovibrio vulgaris, a sulfate reducing bacterium (SRB), in deoxygenated ATCC 1249 medium at 37oC, and using an alga (Chlorella vulgaris) mixed with general heterotrophic bacteria (GHB) in enriched artificial seawater at 28oC. It was found that the coating containing NiMo/CeO2 NPs were much more effective than NiMo in preventing SRB biofilm formation with an efficacy of 99% reduction in D. vulgaris sessile cells after 21-day incubation. The coating also exhibited a 50% lower corrosion current density compared to the uncoated Ti against SRB corrosion. Both NiMo and NiMo/CeO2 NP coatings achieved 99% reduction in sessile algal cells. Confocal laser scanning microscopy (CLSM) biofilm images indicated a large reduction of sessile GHB cells. The CLSM images also confirmed the biocidal kill effects of the two coatings. Unlike polymer coatings, the “metallic” coatings are heat conductive. Thus, the corrosion resistant antifouling coatings are suitable for heat exchanger applications.